Inventory of Fungi on Imported Wheat Grains from Canada at the Large Agricultural Quarantine Center Surabaya - Nirwana Septania Galih Perwira Moekti; Yenny Wuryandari (Future Science, 2023)
Wheat is one of the most popular commodities and is often consumed by the Indonesian people. In 2019, wheat was consumed at least 30.5 kg/year by the Indonesian people. The import of wheat in large quantities allows the risk of carrying OPTK, especially fungi with OPTK category A1, so detection and identification of wheat seeds entering Indonesia is needed. This study aims to detect and determine the fungi found in wheat seeds from Canada (Canada I and Canada II) using the Washing Test method at the Surabaya Agricultural Quarantine Center. The Washing test method is a washing method to release fungi on the surface of seeds using sterile distilled water and a centrifuge. The stages of this method are as follows sampling of wheat seeds from Canada, detection using the washing test method, and microscopic identification. The results of detection and identification on wheat seeds did not find the target pest but other fungi were found in Canada I sample, namely Cladosporium variabile, Cladosporium sp., Puccinia sp., Puccinia graminis and in Canada II sample Cladosporium variabile, and Puccinia graminis. Further quarantine measures for imported wheat grains are exemptions with the issuance of a plant exemption certificate (KT-9). Service procedures at the BBKP Surabaya laboratory are carried out in accordance with Law No. 21 of 2019, MOA No. 25 of 2020 and ISO 17025 with 2P quarantine measures (Inspection and Exemption).